2016
DOI: 10.1093/gerona/glw216
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Seropositivity Predicts a Decline in the T Cell But Not the Antibody Response to Influenza in Vaccinated Older Adults Independent of Type 2 Diabetes Status

Abstract: Type 2 diabetes mellitus (T2DM) and persistent cytomegalovirus (CMV) infection are postulated contributors to inflammatory processes that impact on the age-related decline in T-cell responses to influenza vaccination. Older subjects with T2DM (n = 30) and healthy aged controls (n = 40) were enrolled and received influenza vaccination in this study. Serum inflammatory markers and CMV serostatus were measured. Pre- to post-vaccination changes in serum antibody titers to the A/H3N2 strain, and levels of granzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 37 publications
(45 reference statements)
4
42
0
Order By: Relevance
“…CMV serostatus has been shown to be a key determinant of the Granzyme B (GrB) response to influenza challenge; CMV-seropositive subjects had low levels of inducible GrB activity in response to influenza challenge (Haq et al 2016), suggesting that CMV seropositivity associated with a decline in GrB responses to influenza may predict increased susceptibility to influenza in older adults. CMV seropositivity has also been shown to induce the expansion of polyfunctional CD8+ T cells (CD8+CD57+) secreting multiple cytokines (IFN-γ, TNF-α), which can degranulate in response to stimulation, and are therefore crucial for the generation of optimal responses to infections and vaccines (Pera et al 2014).…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…CMV serostatus has been shown to be a key determinant of the Granzyme B (GrB) response to influenza challenge; CMV-seropositive subjects had low levels of inducible GrB activity in response to influenza challenge (Haq et al 2016), suggesting that CMV seropositivity associated with a decline in GrB responses to influenza may predict increased susceptibility to influenza in older adults. CMV seropositivity has also been shown to induce the expansion of polyfunctional CD8+ T cells (CD8+CD57+) secreting multiple cytokines (IFN-γ, TNF-α), which can degranulate in response to stimulation, and are therefore crucial for the generation of optimal responses to infections and vaccines (Pera et al 2014).…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…Inconsistent findings of the impact of CMV on antibody responses to vaccination have been reported (Wald et al, 2013; Frasca et al, 2015; Furman et al, 2015; McElhaney et al, 2015; Haq et al, 2016). While the influenza B GMT was higher pre-vaccination in CMV − subjects, there was no difference in GMT fold increase (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…We have previosuly shown that GrB levels in unstimulated T-cells (bGrB) are higher is CMV + compared to CMV − older adults (McElhaney et al, 2012; Haq et al, 2016) possibly due to continued activation of CMV-specific T-cells to maintain CMV latency. This study mirrors the previous studies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations